Genetic variability in cassava as it influences storage root yield in Nigeria - Aina, O.O.; Dixon, A.; Akinrinde, E. (Science Alert, 2007)
Genetic variability in shoot and root characteristics among 20 broad-based cassava genotypes was studied in four agroecological zones in Nigeria to determine its effects on root yield. Seventeen agronomic parameters were evaluated on a plot size of 40 m2, at spacing of 1x1 m in a Randomized Complete Block Design (RCBD) in four replicates. Analysis of variance (ANOVA) showed significant differences (p< 0.001) among genotypes within and across locations for most parameters. Significant genotype by environment (GxE) interaction effects was also observed. Estimates of genetic variances for phenotypic and genotypic coefficients of variation were higher for root characters than for shoot characters. PCV ranged from 4.3 to 36.5%; GCV ranged from 3.2 to 22.6%. Broad sense heritability (H2) estimates were high for root characters, ranging from 75 to 88.6%, but low for shoot characters, ranging between 10.6 and 38%. Consequently, considerable scope exists for the improvement of economic traits, such as storage root yield. Shoot traits have little control on storage root yield while root traits with high genetic influence had major control on storage root yield. Number of roots, root size and Harvest Index are major yield determinants to be considered when selecting for root yield in cassava.